2020
DOI: 10.1371/journal.pone.0229883
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition and associated factors among adult patients on antiretroviral therapy follow-up care in Jimma Medical Center, Southwest Ethiopia

Abstract: Background Malnutrition especially undernutrition is the main problem that is seen over people living with HIV/AIDS and can occur at any age. Multiple factors contributed to undernutrition of HIV/ AIDS patients and it need immediate identification and prompt action. The objective of this study was to assess the nutritional status of patients and identify factors associated with undernutrition among HIV/AIDS patients on follow-up care in Jimma medical center, Southwest Ethiopia. Methods A cross-sectional study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 14 publications
5
29
1
Order By: Relevance
“…The double burden of undernutrition and overweight/obesity amongst PLHIV on ART has been reported in previous studies conducted in South Africa, Zimbabwe, Tanzania, and Ethiopia. Consistent with the rates in other studies conducted among PLHIV, the prevalence of overweight/obesity was significantly higher than underweight [34][35][36][37]. Current research shows that the prevalence of adult obesity now exceeds underweight in most countries of the world [38].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The double burden of undernutrition and overweight/obesity amongst PLHIV on ART has been reported in previous studies conducted in South Africa, Zimbabwe, Tanzania, and Ethiopia. Consistent with the rates in other studies conducted among PLHIV, the prevalence of overweight/obesity was significantly higher than underweight [34][35][36][37]. Current research shows that the prevalence of adult obesity now exceeds underweight in most countries of the world [38].…”
Section: Discussionsupporting
confidence: 85%
“…We found that the prevalence of underweight (13%) was contrasted with the higher rates reported in studies in Ghana, Ethiopia, Senegal, and West Africa among PLHIV, where the rates ranged from 23-36%, [11,12,34,42], but were comparable with rates reported in Zimbabwe [37]. The prevalence of undernutrition in males was double (18%) than that of females (9%), although there was no significant association.…”
Section: Discussioncontrasting
confidence: 63%
“…counts (13,27,28). On the other hand, the results of research conducted in the southern part of Ethiopia at Dilla University Hospital indicate that CD4 has no major impact on nutrition (26).…”
Section: Discussionmentioning
confidence: 96%
“…In Ethiopia, studies have been conducted to investigate malnutrition among adult HIV positive individuals (11)(12)(13)(14)(15)(16)(17). However, no study has been conducted on large scale, incorporating a number of health facilities covering large demographic areas and socio-cultural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of intestinal barrier integrity seriously affects the absorption of nutrients, thus hindering the recovery of immune function. Recently, several cross-sectional studies (Mudd and Brenchley, 2016;Gebremichael et al, 2018;Daka and Ergiba, 2020) have shown that the prevalence of malnutrition in patients with HIV/AIDS treated with ART is over 23%, and severe malnutrition amounted to 9%. Further analysis revealed that CD4 + T cell counts below 350 or 200 cells/μl were significantly associated with malnutrition.…”
Section: Effects Of Gut Microbiota Changes On Immune Reconstitution Omentioning
confidence: 99%